Edukasi Pentingnya Peran Suami Dalam Kepatuhan Pemeriksaan ANC Ibu Hamil Di Pulau Pa’jenekang Kabupaten Pangkep - erniawati erni; Sumarni manda; Haerani Rani (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2022)
Antenatal Care is one of the pillars of safe motherhood in an effort to reduce maternal and fetal morbidity and mortality. To make the program successful, the Indonesian government carries out activities such as antenatal care in improving the health quality of pregnant women. Another program that has been launched by the Government of Indonesia is